2021
DOI: 10.1038/s41558-021-01033-6
|View full text |Cite
|
Sign up to set email alerts
|

Critical adjustment of land mitigation pathways for assessing countries’ climate progress

Abstract: Mitigation pathways by Integrated Assessment Models (IAMs) describe future emissions that keep global warming below specific temperature limits and are compared with countries' collective greenhouse gas (GHG) emission reduction pledges. This is needed to assess mitigation progress and inform emission targets under the Paris Agreement. Currently, however, a mismatch of ~5.5 GtCO 2 yr −1 exists between the global land-use fluxes estimated with IAMs and from countries' GHG inventories. Here we present a 'Rosetta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 50 publications
1
76
0
Order By: Relevance
“…Over managed land, the CAMS, UoE and Jena models have a higher sink, CTE and NISMON give similar values, and MIROC gives a smaller sink than over all lands (See Table S1 for the list of models). In contrast, inventory data compiled by Grassi et al (2021) indicates a global land sink of only 0.3 GtC yr -1 . Such a large difference can be possibly explained by the fact that NIs are incomplete (especially in developing countries, and especially non-forest land uses such as cropland, grassland and wetlands) and do not fully capture recent environmental and meteorological effects, such as the impact of more frequent extreme weather events (droughts), and possibly by the lack of actual observation-based estimates in inventories to constrain soil carbon change, in grasslands, croplands and forests.…”
Section: Choice Of Example Countries For Analysismentioning
confidence: 90%
See 4 more Smart Citations
“…Over managed land, the CAMS, UoE and Jena models have a higher sink, CTE and NISMON give similar values, and MIROC gives a smaller sink than over all lands (See Table S1 for the list of models). In contrast, inventory data compiled by Grassi et al (2021) indicates a global land sink of only 0.3 GtC yr -1 . Such a large difference can be possibly explained by the fact that NIs are incomplete (especially in developing countries, and especially non-forest land uses such as cropland, grassland and wetlands) and do not fully capture recent environmental and meteorological effects, such as the impact of more frequent extreme weather events (droughts), and possibly by the lack of actual observation-based estimates in inventories to constrain soil carbon change, in grasslands, croplands and forests.…”
Section: Choice Of Example Countries For Analysismentioning
confidence: 90%
“…For this study, intact forest areas (that are unmanaged, by definition) were removed from the CO2 totals, in proportion to their presence in each inversion grid box, based on the Intact Forest Landscapes maps of Potapov et al (2017) shown in Figure S1. This approach assumes that non-intact forest represents a reasonably good proxy of managed forest reported in national GHG inventories (Grassi et al, 2021). In the absence of a machine-readable definition of the plots considered to be managed in many NIRs, this choice remains somewhat arbitrary and other unmanaged land datasets could have been used (Ogle et al, 2018;.…”
Section: National Masks -Fossil Fuel Emissions Regridding -Managed Land Maskmentioning
confidence: 99%
See 3 more Smart Citations